2018
DOI: 10.3390/s18010249
|View full text |Cite
|
Sign up to set email alerts
|

Use of Accelerometer Activity Monitors to Detect Changes in Pruritic Behaviors: Interim Clinical Data on 6 Dogs

Abstract: Veterinarians and pet owners have limited ability to assess pruritic behaviors in dogs. This pilot study assessed the capacity of the Vetrax® triaxial accelerometer to measure these behaviors in six dogs with pruritus likely due to environmental allergens. Dogs wore the activity monitor for two weeks while consuming their usual pet food (baseline), then for eight weeks while consuming a veterinary-exclusive pet food for dogs with suspected non-food-related skin conditions (Hill’s Prescription Diet® Derm Defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Commercially available accelerometers designed for use in dogs have gained popularity as a means to track daily activity and monitor overall fitness and health. Accelerometers have been utilized to objectively measure physical activity and track‐specific movements in dogs involved in studies on behavior, pruritis, osteoarthritis, and weight loss . The aim of our study was to evaluate the use of accelerometry to detect seizure activity in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available accelerometers designed for use in dogs have gained popularity as a means to track daily activity and monitor overall fitness and health. Accelerometers have been utilized to objectively measure physical activity and track‐specific movements in dogs involved in studies on behavior, pruritis, osteoarthritis, and weight loss . The aim of our study was to evaluate the use of accelerometry to detect seizure activity in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The HDD diet is designed to contain whole egg, antioxidants and sources of polyphenols as ingredients chosen for their ability to improve skin barrier function and lower inflammation canine AD (WERNIMONT et al, 2018). In 2014, Plevnik et al reported low plasma vitamin E levels in dogs with AD (PLEVNIK et al, 2013) and supplementation with 8.1 IU/kg vitamin E once daily orally reduced the clinical scores in AD dogs (PLEVNIK et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of nutritional management for canine AD is to inhibit the inflammatory response, stabilize the skin barrier and support skin and coat health (OLIVRY et al, 2015). New veterinary-exclusive pet food for dogs with allergic skin disease (Hill's Prescription Diet ® Derm Defense TM Canine dry food; (Hill's Pet Nutrition Inc., Topeka, KS, USA) has been released onto the pet food market (WERNIMONT et al, 2018). The Hill's Derm Defense (HDD) diet contains a proprietary blend of whole egg, antioxidants and sources of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations